Solutions to Big Data Privacy and Security Challenges Associated With COVID-19 Surveillance Systems - Bentotahewa, Vibhushinie; Hewage, Chaminda; Williams, Jason (Frontiers in Big Data, 2021)
The urgent need to find solutions to overcome the effects of the Coronavirus necessitate collecting data in large volumes. On the one hand Big Data acquisition and storage poses an apparent significant threat to privacy of individuals, and on the flipside, it helps make important decisions for prevention of COVID-19. Data protection law faces many challenges in the digital age, and the emergence of Big Data is the most conspicuous and challenging. In the Big Data era, the public enjoys many benefits that internet technology offers to them, and at the same time, they also do face potential breeches of privacy laws affecting personal data. Amongst the technologies used in combating the pandemic the focus should also be on the impact of facial recognition cameras, police surveillance drones and other digital surveillance devices. It is noticeable that a few countries have employed digital surveillance technologies for the purpose of tracking and monitoring individuals and populations to control the spread of the Coronavirus. But the key intake is, whoever using whatever mechanism will be infringing on public privacy in one way or another. In practical terms, the technology may have the capacity to contribute to tackle the pandemic effectively, but it comes at the expense of privacy rights violations. The biggest issue of concern is visualising the degree of surveillance and what surprises it is likely to bring. The privacy experts also have raised concerns about how the governments were using the data, the storage methods and how the authorities would maintain heightened levels of surveillance in post coronavirus pandemic. This paper focuses on Big Data challenges associated with surveillance methods used within the COVID-19 parameters. The aim of this research is to propose practical solutions for Big Data challenges associated with surveillance approaches within the realm of COVID-19 pandemic. To that end, the researcher will identify the surveillance measures being used by countries in different regions, the sensitivity of generated data and the issues associated with the collection of large volumes of data and, finally to propose feasible solutions to protect the rights of people to privacy during post-COVID-19 era.